Something in the Pipe: Flint Water Crisis and Health at Birth - Rui Wang; Xi Chen; Xun Li (Global Labor Organization (GLO), 2021)
In 2014, the city of Flint, MI in the U.S. changed its public water source, resulting in severe water contamination and a public health crisis. Using the Flint Water Crisis as a natural experiment, we estimate the effect of in utero exposure to polluted water on health at birth. Matching vital statistics birth records with various sources of data, we use a Synthetic Control Method (SCM) to identify the causal impact of water pollution on key birth outcomes. Our results suggest that the crisis modestly increased the rate of low birth weight (LBW) by 1.8 percentage points (or 15.5 percent) but had little effect on the length of gestation or rate of prematurity. However, these effects are larger among children born to black mothers, as indicated by an increase in the rate of LBW by 2.5 percentage points (or 19 percent). Children born to white mothers exhibit, on average, a 30.1-gram decrease in birth weight. We find little evidence that the male-to-female sex ratio declines in the overall population, suggesting that the inutero scarring effect of the Flint Water Crisis may dominate the channel of mortality selection. However, we observe a slight decline in the sex ratio among children born to black mothers. Finally, we find no notable change in the fertility rates of either black women or white women in Flint. These results are robust to a rich set of placebo and falsification tests. Our findings highlight the importance and urgency of upgrading U.S. aging, lead-laced water systems in promoting racial and ethnic health equity.
Keywords: I14; I18; Q53; Q58; 330; water pollution; lead exposure; Flint Water Crisis; infants; low birth weight